(untitled) (East West Medical College Journal, 2026)
Context: Accurate knowledge of orbital morphometry is essential for the evaluation, diagnosis, preoperative planning, and intraoperative management of craniofacial syndromes, post-traumatic facial deformities, and orbital abnormalities, with the goal of achieving optimal aesthetic and functional outcomes. This knowledge is also relevant to anesthesiologists performing ocular surgeries, particularly when employing various nerve blocks, and is valuable to anthropologists, ophthalmologists, anatomists, forensic experts, and maxillofacial and reconstructive cosmetic surgeons. Safe and effective orbital surgery requires a thorough understanding of the bony orbit’s anatomy and the morphometric relationships within it. Objective: Primary objective: To perform a photo-anthropometric analysis of the lateral wall of fully ossified dry human orbital cavities by measuring selected anatomical landmarks. Secondary objectives: To evaluate the morphometric differences between the right and left lateral orbital cavities and to establish baseline morphometric data for anatomical, forensic, and clinical application. Materials & Methods: A cross-sectional analytical study was conducted in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2014 to June 2015. The study was performed on 200 fully ossified dry orbital cavities from 100 human skulls. Results: In the present study, the mean distance from the frontozygomatic (FZ) suture to the lateral margin of the optic canal (OC) was 46.65±2.75 mm on the right side and 46.41±2.44 mm on the left side. The difference between the right and left orbital cavities was significant (p<0.05). The mean distance from the frontozygomatic (FZ) suture to the closest margin of the superior orbital fissure (SOF) was 38.83±3.25 mm on the right and 38.69±3.16 mm on the left. No significant difference was observed (p>0.05) for this distance. Conclusion: The lateral orbital wall exhibits significant asymmetry in FZ–OC distance (p<0.05). These normative data serve forensic experts in skull identification and trauma analysis, anthropologists in ethnic and evolutionary studies, and anatomists in surgical education and morphological reference. The validated photographic method (MAPE <3%, ICC >0.95) offers a reliable, non-invasive alternative to direct caliper measurement. EWMCJ Vol. 14, No. 2, July 2026: 191-196